Seroepidemiological study of toxoplasma in Iraqi patients (Journal of the College of Basic Education, 2022)
The epidemiology of ocular toxoplasmosis was studied for Iraqian patients at Ibn Al-Haitham hospital of eyes in Baghdad, from December 2013 to May 2014. The number of patients that reviewing retain until was 104 patients and 96 individual as a control group. The age ranged from 5 to 80 year. The infection was diagnosed clinically and some epidemiological characters were studied like age, sex, educational level and residency with their relationship to infection. The results of clinical diagnosis was confirmed by immunological tests Latex and ELISA with the presence of IgG antibody. Age has a little effect on ocular toxoplasmosis group with mean 38.07±15.14, highly significant differences with occupations include (house wife and workers). With a percentage 70% was recorded. The most of ocular toxoplasmosis and uveitis samples were found in highly frequency at primary, intermediate and secondary educational level with a total rate 74% and 77.8% respectively. The living was focus in the middle region with a rate 92% for patients due to the site of hospital in Baghdad province. The presence of animals especially cats leading to statistical differences with infection. The visual acuity and intraocular pressure didn’t cause significant differences with the infection. The results of Latex and ELISA testes were compared the Latex test is easier and faster in diagnosis of ocular toxoplasmosis while ELISA test was more sensitive, and according to its results the main groups were divided to sub groups, the IgG level of ocular toxoplasmosis group was 2.972±2.416 Iu/ml while in sub clinical group 3.186±1.7 Iu/ml and uveitis group 0.637±0.803 in comparable with negative control group 0.276±0.163. The IgM level was low and its presence didn’t have any positive case. The IgG level has a relationship with a pathological effect on eyes in ocular to toxoplasmosis and uveitis groups, it was high rate 73.5% with 50 patient for posterior uveitis causing a significant differences followed by anterior uveitis with rate 13.2%.